Des surbordonnées en if compléments non interrogatifs ? - Anne Jugnet (Anglophonia)
Clauses introduced by if are traditionally assigned two functions: they are analyzed either as conditional adjuncts or as (indirect) interrogative complements. Yet in some structures the status of the if clause is not clear-cut, since the clause seems to describe (indirectly) the object argument of the embedding verb, but is clearly not interrogative (as it seems semantically similar to a conditional). These cases have often been overlooked in the literature. Our aim is to show that a third type of if clauses should be contemplated, i.e. if clauses that are complements of embedding verbs even though they do not involve epistemic questioning. A tripartite categorization is thus put forward.